Statistically-informed deep learning for gravitational wave parameter estimation. Issue 1 (30th November 2021) - Shen, Hongyu; Huerta, E A; O'Shea, Eamonn; Kumar, Prayush; Zhao, Zhizhen
Abstract: We introduce deep learning models to estimate the masses of the binary components of black hole mergers, ( m 1, m 2 ), and three astrophysical properties of the post-merger compact remnant, namely, the final spin, a f, and the frequency and damping time of the ringdown oscillations of the fundamental ℓ = m = 2 bar mode, ( ω R, ω I ) . Our neural networks combine a modified WaveNet architecture with contrastive learning and normalizing flow. We validate these models against a Gaussian conjugate prior family whose posterior distribution is described by a closed analytical expression. Upon confirming that our models produce statistically consistent results, we used them to estimate the astrophysical parameters ( m 1, m 2, a f, ω R, ω I ) of five binary black holes: GW150914, GW170104, GW170814, GW190521 and GW190630 . We use PyCBC Inference to directly compare traditional Bayesian methodologies for parameter estimation with our deep learning based posterior distributions. Our results show that our neural network models predict posterior distributions that encode physical correlations, and that our data-driven median results and 90% confidence intervals are similar to those produced with gravitational wave Bayesian analyses. This methodology requires a single V100 NVIDIA GPU to produce median values and posterior distributions within two milliseconds for each event. This neural network, and a tutorial for its use, are available at the Data and Learning Hub for Science .